2000
DOI: 10.1148/radiology.217.3.r00dc06855
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Calcaneal Trabecular Bone Structure after Heart Transplantation: An MR Imaging Study

Abstract: MR imaging-derived structure measurements in the calcaneus are useful for monitoring bone changes after heart transplantation and assessing vertebral fracture status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Emerging data indicate that bone microarchitecture offers important information about bone fragility [1114]. Several studies have demonstrated increased fracture risk associated with abnormal bone microarchitecture and normal BMD, suggesting that microstructure may be a more sensitive measure than BMD in assessing such risk [20]. Parameters of bone microarchitecture are also abnormal in postmenopausal and corticosteroid-induced osteoporosis [21, 22] and are associated with increased fracture risk independent of BMD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data indicate that bone microarchitecture offers important information about bone fragility [1114]. Several studies have demonstrated increased fracture risk associated with abnormal bone microarchitecture and normal BMD, suggesting that microstructure may be a more sensitive measure than BMD in assessing such risk [20]. Parameters of bone microarchitecture are also abnormal in postmenopausal and corticosteroid-induced osteoporosis [21, 22] and are associated with increased fracture risk independent of BMD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, a 3-dimensional (3D) excitation usually provides higher SNR than a 2D sequence. However, 2D acquisition techniques have also been used previously to image the trabecular structure of the calcaneus (1719) albeit with lower spatial resolution. Secondly, the gradient-echo has to be acquired immediately after the excitation pulse in order to avoid signal loss due to T2 relaxation.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Studies in other populations, such as transplant patients [45], hypogonadal men [46], and patients with osteoarthritis [34] have also been initiated, as the promise of assessing trabecular bone microarchitecture noninvasively has clearly been established over the past decade. Chesnut et al [17••] published the first longitudinal study showing that nasal spray calcitonin preserves trabecular bone microarchitecture in the distal radius.…”
Section: Clinical Relevance Of Bone Microarchitecturementioning
confidence: 99%